Software resources for lighting design. - Laiserin, Jerry (Architectural Record, 2001)
Focuses on lighting design software. Use of lighting and analysis software to simulate the physical behavior of light as it interacts with forms and surfaces of varying shapes, textures and colors; Application of software procedures or algorithms to the geometry of a building or interior space to calculate the light energy falling on a surface from any light source.